2004
DOI: 10.1097/00000478-200405000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Mesonephric Tumors of the Female Genital Tract

Abstract: Nine malignant mesonephric tumors were obtained from the consultation files of one of the authors (J.P.) over a 13-year period (1988-2001). There were 4 adenocarcinomas (ACs) and 5 malignant mixed mesonephric tumors (MMMTs). The ACs were found in the cervix (3) and vagina (1). The MMMTs involved the uterus (1), cervix (3), and vagina (1). Most patients presented with abnormal vaginal bleeding. The 4 patients with mesonephric AC ranged in age from 24 to 54 years (mean, 41 years). The tumors measured 2 to 6 cm (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
104
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 10 publications
1
104
1
1
Order By: Relevance
“…6 Our study found no correlation between the molecular features of mesonephric carcinoma and presence of a spindled/solid component, but this could potentially be attributed to the fact that most of the cases had only one slide of tumor available for review, which may have not been representative of the overall morphological appearances of the neoplasm.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…6 Our study found no correlation between the molecular features of mesonephric carcinoma and presence of a spindled/solid component, but this could potentially be attributed to the fact that most of the cases had only one slide of tumor available for review, which may have not been representative of the overall morphological appearances of the neoplasm.…”
Section: Discussioncontrasting
confidence: 72%
“…1-3 Primary mesonephric carcinomas of the uterine corpus and the vagina have also been described. [4][5][6][7][8] Patients with mesonephric carcinoma usually present with abnormal vaginal bleeding (in~60-70% of the cases), abnormal Papanicolaou smear, a cervical mass on pelvic examination, or the tumor can be discovered incidentally. 1,2 Grossly, these tumors are frequently in the form of an exophytic, nodular, or polypoid friable mass usually in the lateral wall of the cervix or involving the cervical wall circumferentially.…”
mentioning
confidence: 99%
“…These authors proposed that corpus MA originated from Müllerian tissue and obtained the morphological and immunohistochemical phenotype characteristic of mesonephric differentiation; this tumor is described as a 'mesonephric-like adenocarcinoma' rather than MA. In addition to that case, 10 additional cases of corpus MA, including the present tumor, have been reported [2][3][4][5][6][7][8]10]. While one case was believed to be derived from the endometrium, the epicenter of five tumors was in the myometrial layer [5,6,8,10], and three tumors were completely confined to the myometrial layer [2,3] (Table 2).…”
Section: Discussionmentioning
confidence: 73%
“…A leiomyoma nodule is observed immediately to the left [12]. Few cases of MA have been reported in the uterine corpus [2][3][4][5][6][7][8][9][10]. A unique histologic pattern of uniform small tubules containing intraluminal hyaline material is reminiscent of mesonephric remnants [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation